Comparison of Insulin Detemir and Insulin Glargine for Hospitalized Patients on a Basal-Bolus Protocol - Sondra Davis; Chad Friece; Nicki Roderman; Darrell Newcomer; Evangelina Castaneda (MDPI AG, 2017)
BACKGROUND: The primary purpose of this study is to determine whether insulin detemir is equivalent to insulin glargine in controlling hyperglycemia for the adult hospitalized patient on a basal-bolus treatment regimen. METHODS: A retrospective study was conducted at two acute care hospitals within the same health system. Patients from both facilities who were initiated on a basal-bolus subcutaneous insulin regimen were included in the study. The basal-bolus regimen consisted of three components: basal, bolus, and corrective insulin with only the data from the first seven days analyzed. Once the basal-bolus protocol was initiated, all previous glycemic agents were discontinued. The target glycemic goal of the study was 100-180 mg/dL. RESULTS: In both groups, 50% of the patients had achieved the target glycemic control goal (100-180 mg/dL) by day 2 (p = 0.3). However, on the seventh or last day of basal-bolus treatment, whichever came first, 36.36% of patients receiving insulin detemir (n = 88) achieved the blood glucose reading goal compared to 52.00% in patients receiving insulin glargine (n = 100) (p = 0.03). This corresponded to an adjusted odds ratio of 2.12 (1.08 to 4.15), p = 0.03. The adjusting variables were provider type, whether the patient was hospitalized within 30 days prior and diagnosis of stroke. The mean blood glucose readings for the insulin glargine and the insulin detemir groups while on basal-bolus therapy were 200 mg/dL and 215 mg/dL, respectively (p = 0.05). The total number of blood glucose readings less than 70 mg/dL and less than 45 mg/dL was very low and there were no differences in number of episodes with hypoglycemia between the two groups. CONCLUSION: There was not a statistical difference between the two groups at 2 days, however there was on the seventh day or the last day of basal-bolus treatment. There were nonsignificant hypoglycemia events between basal insulin groups and the results for the last or seventh day of treatment may not be clinically significant in practice.